The Women Who Built Omaha A Bold and Remarkable History - Wirth, Eileen M., 1947- (Book collections on Project MUSE., 2022)
"The Women Who Built Omaha explores the important contributions of women to Omaha while placing those contributions in the context of social history. Wirth describes the activities of local women in numerous fields from the 1850s to the modern women's movement in the 1970s, bringing to life those who have been overlooked throughout history"--